Aspectos innovadores en el dise˜no y construcción del dique Oeste en el puerto exterior de A Coru˜na en Punta Langosteira (Espa˜na). Issue 2 (1st July 2016) - Santos, M.; Corredor, A.; Maciñeira, E.; Bajo, V.; Gómez-Martín, M.E.; Medina, J.R.
Abstract: This article describes the innovative aspects in design and construction of the western breakwater of the outer port at Punta Langosteira (A Coru˜na, Spain). The secondary breakwater is formed by the south breakwater (1. st phase) and the western breakwater (2. nd phase), currently under construction, and it is intended to complete the shelter provided by the main breakwater of the outer port of A Coru˜na and to ensure high operability of the new port facilities, as well as to contain the movement of the beaches to the west of the port. The bidding process, which permitted variations to the preliminary design, favors innovation, allowing for a variety of solutions based on the use of different armor units, and cubipods were finally selected for the main armor layer. The 1.35 km long secondary breakwater is protected by a single-layer 25 t and 30 t cubipod armor in the trunk, and a double-layer 45 t cubipod armor in the roundhead. The alternative cubipod solution allows for a breakwater which withstands wave climates higher than the defined limit state (Hs =8.75 m in the trunk) and significantly reduces the economic cost and the concrete consumption. In order to optimize and validate the alternative solution, 3D hydraulic stability and overtopping test were performed with 1/51 scale, similar to those made to justify the preliminary design by the port authority. 1, 360 cubipod units (15-and 25-tonne) from the southern and northern breakwaters, which are now sheltered by the new breakwater, have been reused at the western breakwater. A transition single-to double-layer armor has been constructed, with opposite fitting, increasing progressively the thickness of the filter layer to maintain a homogeneous exterior surface of the armor when modifying the armor thickness.